A New Technology Separating Allelopathy From Competition in Pot Experiments - Jamal R Qasem (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2017)
A new technology is developed to separate allelopathy from competition in pot experiments. Square pots of any sizes may be used. Each pot is divided by a metal or pvc mesh (100-150 micrometer) barrier fixed from the bottom to pot surface. The barrier divides the pot into two sections filled by the same amount of soil mixture. Seeds or seedlings of the donor and receiver species can be planted separately each in a pot  section. Density of the donor plant can be varied as required. Nutrient solution can be equally and uniformly added to both pot sections. At an extended period, another similar barrier can be also inserted from the above pot surface to prevent shoot competition. In the control, both receiver and donor plants can be separately grown in divided pots and treated similarly as in other treatments. The technique prevents donor invasion into receiver section and differentiate non-allelopathic from allelopathic species. Failure of receiver species to perform or attain normal growth may be regarded as an indicator on possible allelopathy effects of the donor species. All kinds of comparisons and combinations can be tested and under both normal and stress conditions. A diagram of the new technique separating allelopathy from competition is illustrated.